DOES BOARD COMPOSITION AND OWNERSHIP STRUCTURE MATTER IN RISK DISCLOSURE LEVEL: EVIDENCE OF TUNISIAN FIRMS - Ahmadi, Ali (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2024)
ABSTRACT The main objective of this study is to examine the diversity of boards of directors and the ownership structure of Tunisian companies. The study uses 2019 company-level data of Tunisian companies listed in the stock market risk disclosure levels are captured by manual content analysis in annual reports. This article considers the risk disclosure level based on a sample of 53 companies listed on the Tunisian stock exchange. Regression analysis shows that the corporate governance mechanisms in our study are significantly associated with the level of risk disclosure. The results show that usually board independence, institutional ownership, foreign ownership positively affect the level of risk disclosure. However, the size of the board of directors is negatively associated with the level of risk information disclosed in annual reports. This study contributes to the existing literature on accounting for corporate disclosure strategy. This study provides new evidence on how board composition and ownership structure affect the level of risk disclosure. ABSTRAK Tujuan utama dari studi ini adalah untuk menguji keberagaman dewan direksi dan struktur kepemilikan perusahaan-perusahaan Tunisia. Studi ini menggunakan data tingkat perusahaan tahun 2019 dari perusahaan-perusahaan Tunisia yang terdaftar di pasar saham. Tingkat pengungkapan risiko ditangkap oleh analisis konten manual dalam laporan tahunan. Artikel ini memperhitungkan tingkat pengungkapan risiko berdasarkan sampel 53 perusahaan yang terdaftar di bursa saham Tunisia. Analisis regresi menunjukkan bahwa mekanisme tata kelola perusahaan dalam studi kami secara signifikan terkait dengan tingkat pengungkapan risiko. Hasilnya menunjukkan bahwa biasanya independensi dewan, kepemilikan institusional, kepemilikan asing secara positif memengaruhi tingkat pengungkapan risiko. Namun, ukuran dewan direksi secara negatif terkait dengan tingkat informasi risiko yang diungkapkan dalam laporan tahunan. Studi ini berkontribusi pada literatur yang ada tentang akuntansi untuk strategi pengungkapan perusahaan. Studi ini memberikan bukti baru tentang bagaimana komposisi dewan dan struktur kepemilikan memengaruhi tingkat pengungkapan risiko